PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI CERITA ANAK SISWA KELAS V SDIT INSAN UTAMA PEKANBARU - Wiyana Muliani; Otang Kurniaman; Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The problem this research is the students achievement of social fifth graderes studies still low with an average value of 68,1 and minimum completeness criteria (KKM) social studies is 70. Between students, amounting to 21 people only 8 students who achieve classical KKM with 38,1%. This research is Classroom Action Research (CAR), which aims to improve the student achievement of social studies class V at SDIT Insan Utama Pekanbaru with implementation cooperative learning model type numbered heads together. Formulation of the problem : Is the implementation of cooperative learning model type numbered heads together can improve students achievement of social studies class V at SDIT Insan Utama Pekanbaru? The research was conducted on January 11 to January 21 by 2 cycles. Subjects were students of SDIT Insan Utama Pekanbaru, totaling 21 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 68,1. In the first cycle improve an average of 76,43 with increase big as 8,33% and an improve in the second cycle with an average of 86,14 with increase big as 9,71%. Activities of the teacher in the learning process in cycle I first meeting improve to 50 % and the second meeting improve to 62,5%. Cycle II first meeting improve to 82,5% and the second meeting improve to 92,5 %. Results of data analysis of students activities in the first cycle with the first meeting of an average of 50% and a second meeting improve to 62,5%. Second cycle first meeting improve to 82,5% and the second meeting improve to 92,5%. Results in the class V at SDIT Insan Utama Pekanbaru that the implementation of cooperative learning model of Numbered Heads Together can improve the student achievement of social studiesat fifth graderes SDIT Insan Utama Pekanbaru.Key Words: Model Learning Numbered Heads Together, fifthh graderes Students Achievement.